The Bible on leadership : from Moses to Matthew : management lessons for contemporary leaders - Woolfe, Lorin (American Management Association, 2002)
Moses on vision. John the Baptist on communication skills. Queen Esther on political know-how. Great leaders from the Bible have powerful lessons to teach today's business leaders.